Chemical Components of some Hydrola (Distillated Waters) from Iranian Medicinal Plants: Chemical Components of some Hydrola from Iranian Medicinal Plants - Mojab, Faraz; Hossein-abadi, Tahereh; Farhadi, Zahra; Ghashghaee, Davood (Iranian Journal of Pharmaceutical Sciences, 2021)
Medicinal distilled waters (hydrola) are substances prepared by distilling water in the presence of aromatic plants or plants without fragrance. In Iran, these waters are often used for medicinal properties. Their taste and smell are similar to plants and volatile substances from which aromatic water is prepared. Some of these aromatic waters have been studied previously. In this manuscript, we have analyzed some hydrolas from some medicinal herbs in Iranian Traditional Medicine. It may be used to identify and standardize such waters. The hydrolas of 13 Iranian medicinal herbs were prepared and analyzed by GC/MS. Major components of Tripleurospermum disciforme, Citrus aurantium, Alhagi pseudoalhagi, Foeniculum vulgare, Cuminum cyminum, Bunium persicum, Cichorium intybus, Mentha spicata, Anethum graveolens, Salix aegyptica, Zataria multiflora, Rosa damascana and Fumaria parviflora were identified. It is the first report analysis of some hydrola from Iranian medicinal plants except for rose water. This analysis may be a help to the standardization of high-consumption aromatic waters.